PERSPEKTIF MAKASSAR: SEBUAH KEMUNGKINAN TEORI HI NON-BARAT - Edi Abidin; Asma Amin (WANUA : Jurnal Hubungan Internasional, 2017)
Today’s International Relations perspectives mostly dominated by eurocentric point ofview. These perspectives, become the core of IR studies and not realized by scholars from many non-Western countries in the studies and keep them away from their own“realities” in their analysis. The rise of Global IR opens some new possibilities to develop an inclusive perspective where non-Western might have their own point of view based on their own context. Using Global IR as a stepping stone, this article tries to elaborate the history of Makassar in the 17th century and its place in Southeast Asia history and to connect it with the rise of ASEAN.